Dystopian Imagery of Political, Ecological, and Social Criticism: Iconographies in Galician Graphic Art - Gil Martínez, María (Madrygal. Revista de Estudios Gallegos, 2023)
When we talk about graphic or printed art, we are referring to a series of materials that move between the fields of plastic art and literature, between a work of art and a document, and they are usually made in cheap and ephemeral formats, such as: posters, fanzines, magazines, pamphlets, and comic books. In Galicia, they were used as a place for experimentation, especially from the 70s on: they provided a space for political criticism, dissent, and the search for freedom of speech, avoiding this way the censorship imposed by dictatorship until those days. Social movements could be voiced and disseminated in Galician graphic art. The antifascist, nationalist, social, economic, feminist, and ecological political struggles had a significant presence in edition through particular iconographies that, on many occasions, followed the idea of dystopia. Time travel, anachronisms and imagined futures served as ironic metaphors of a harsh reality, full of problems that had to be exposed and fought. From 2 viaxes, by Xaquín Marín and Reimundo Patiño, to the Nunca Máis response to the Prestige catastrophe, printed paper has collected dystopian images as predictions of an apocalyptic future that we fear in the present. This paper provides an overview in order to look at the similarities and the differences between various examples, which will help to understand what happened in anti-establisment art in times of greatest social upheaval.